PROSES BERPIKIR INTUITIF SISWA OLIMPIADE SMP DALAM MENYELESAIKAN SOAL HIGH ORDER THINKING (HOT) MATEMATIKA - Siti Nurfaiza; Zainal Abidin; Khusnul Safrina (Prodi Pendidikan Matematika Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2025)
Olympiad competitions usually present problems that require high-order thinking (HOT) skills. To solve them, students need skills, ideas, and creativity, so not all can answer spontaneously. Therefore, it is important to examine the intuitive thinking process of students in solving HOT problems. This qualitative study aims to describe the intuitive thinking process of junior high school Olympiad students in solving HOT mathematics problems. Data were collected through tests and interviews with students who had won or participated in the 2019 Madrasah Science Competition (KSM) at the MTs level. The findings show that Olympiad students can understand problems directly and spontaneously. In planning solutions, they use intuition such as common sense, intrinsic certainty, and extrapolativaness. They then implement solutions with common sense and extrapolativaness, and verify their answers using globality and coerciveness.